The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/pssa.201600486
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dopant segregation on the work function and electrical properties of Ge-doped in comparison to Sn-doped In2O3thin films

Abstract: Ge‐doped In2O3 thin films prepared by magnetron sputtering are studied using photoelectron spectroscopy and Hall effect measurements. Carrier conductivities of up to 8.35thinmathspace×thinmathspace103cm−1 and carrier mobilities of up to 57thinmathspacecm2thinmathspaceV−1s−1 are observed. The surface Ge concentration is enhanced by a factor of 2–3 compared to the concentration in the interior of the films. The surface Ge concentration increases with more oxidizing deposition conditions, in opposite to what has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…All the examples given in this section so far concerned Sn doped indium oxide, as it is currently the benchmark materials for inorganic transparent electrodes. However, it has been shown that indium oxide can also be efficiently doped by other elements such as Si, Ga or Mo [34][35][36][37] .…”
Section: Figure 3 Evolution Of Resistivity Carrier Concentration and Carrier Mobility (Hall Mobility) Inmentioning
confidence: 99%
See 1 more Smart Citation
“…All the examples given in this section so far concerned Sn doped indium oxide, as it is currently the benchmark materials for inorganic transparent electrodes. However, it has been shown that indium oxide can also be efficiently doped by other elements such as Si, Ga or Mo [34][35][36][37] .…”
Section: Figure 3 Evolution Of Resistivity Carrier Concentration and Carrier Mobility (Hall Mobility) Inmentioning
confidence: 99%
“…Gallium doped In2O3 for instance, was reported to display conductivities in the range of 10 3 to 10 4 Scm -1 and extremely high electron mobilities of 50 cm 2 V -1 s -1 [34,36,37] , whereas doping of In2O3 with molybdenum resulted in improved transmittance in the visible regime as compared to tin doped InO [35] . deposited via an aqueous sol-gel process.…”
Section: Figure 3 Evolution Of Resistivity Carrier Concentration and Carrier Mobility (Hall Mobility) Inmentioning
confidence: 99%
“…Nevertheless, according to DFT calculations [28][29][30]33], one would expect some differences between [110]and [111]-oriented films, which both exhibit flat surfaces. A possible explanation for the independence on surface orientation is the segregation of the Sn dopant to the surface, which is particularly observed under reducing conditions [34][35][36]. A different surface composition will affect the surface dipole.…”
Section: Ito Surface Potentialsmentioning
confidence: 99%
“…Significant difference of the ionization potential I P , which is the difference between the valence band maximum and vacuum energy, between the [100] and [111]-surfaces of In 2 O 3 could be observed as well [29]. The situation is more complex for doped In 2 O 3 due to dopant segregation [30,[34][35][36]. Some authors [17,37] suggested that a surface treatment of the substrate may enhance the stability of the organic molecules.…”
Section: Introductionmentioning
confidence: 99%
“…The electrical conductivity can be significantly enhanced to approximately 1000 S cm −1 by alloying with Sn, which is known as indiumtin-oxide (ITO). There are also reports on the improvement of electrical conductivity by alloying with different elements, such as Ti [29], Ge [30], and Mo [31]. However, the thermal conductivity of In 2 O 3 -based materials is generally high, which is an obstacle for thermoelectric applications.…”
mentioning
confidence: 99%